Prevzemi in sodna praksa - Balažic, Vlado (Podjetje in delo, 2015)
When confronted with cases from the field of companies' take-overs the Slovenian courts have dealt mainly with two sets of issues. The first is reaching the take-over threshold, with particularly problematic question regarding converted action of several subjects in order to gain control over the offeree company and a related (non)execution of the voting rights. The second set of such issues is the exclusion of minority shareholders from the offeree company, especially with regard to the determination of a fair severance pay.
Keywords: delničarji; podjetja; pravna ureditev; prevzem